O discurso da divulgação científica em jornais de distribuição gratuita: o caso do jornal Bem Estar - Alves, Lêda Araújo (Universidade do Vale do Rio dos Sinos, 2015)
This study aims to analyze the linguistic and discursive organization of published texts in the newspaper “Bem Estar” in order to verify if these texts, which deal with human health, can be classified as Science Communication texts. The corpus consists of three reports extracted from this free newspaper published between the years 2013 and 2014. We assume the theoretical proposal of Charaudeau (2013), especially the notion of communication agreement as recognition of the achievement of linguistic trading conditions and media contract. The research proposed here focuses on this field by proposing the identification and the description of the textual-discursive functioning objects of speech present in the texts that, due to their production conditions, circulation and reception, require you to take into consideration the constraints of the Mediatic Scientific Communication: aims of captation and information, which constitute the contract of media communication. Besides this semiolinguistic analysis, we find linguistic marks of Enunciative Responsibility and Argumentative Orientation on the selected texts, subsidized by the Textual Analysis of the Discourses postulated by Adam (2011), which will help us understand how the enunciator of the texts makes use of discursive strategies that indicate Enunciative Responsibility. For this analysis, we chose two categories that characterize the textual materiality: the subject marks and the indications of mediator’s frames, in which you can tag the linguistically detachment or engagement of the enunciator on the expressed information. Thus, it follows that this (not) claiming of responsibility guides the argumentative organization of the enunciator influencing and establishing its communicative purposes.
Keywords: Divulgação científica; Contrato de comunicação; Responsabilidade enunciativa; Science communication; Communication contract; Enunciative responsibility; ACCNPQ::Lingüística, Letras e Artes::Lingüística